The double helix : a novel - Trueit, Trudi Strain (Trueit, Trudi Strain. Explorer Academy, 2019)
"A mysterious person alerts Cruz to impending danger while he and a few trusted pals explore ancient ruins in Petra, Jordan, and search for another piece of the puzzle his mother left behind. Worst of all, now his father has gone missing, which prompts Aunt Marisol, his number one protector, to leave the ship in search of him"--Provided by publisher.